Optimalisasi Antrian Perawatan Mobil Ford Menggunakan Model Single Channel Single Phase (SCSP) (Studi Kasus Bengkel September Auto Service Bandar Lampung) - Sri Cahyo Hadi K (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2022)
The September Auto Service (SAS) workshop has a problem, namely the process of queuing for ford car services and maintenance is done manually, so it has an impact on vehicles queuing, it is difficult to see the history of vehicles that have been repaired. In addition, providing information to customers can only be given orally, if there are customers who want to ask about the progress of vehicle repairs, they must be by telephone or come directly sometimes not always responded to because the customer population is so large and in making purchase reports, sales reports and service reports. the vehicle is still manually. Therefore, the SAS workshop should provide innovations to deal with these problems. In its development, the author uses the extreme programming method, as well as for the approach to making the system using an object-based programming paradigm, with a design using UML. a website-based queuing system can help overcome the difficulties of queuing and the vehicle repair/service process because of the application of the Single Channel Single Phase concept which plays a role when inspecting ford car vehicles, and this system can also manage the purchase and sale of ford car spare parts, assisting customers in monitoring the progress of repair work vehicles and provide faster and more accurate purchase, sales and service reports